Analysis of The Influence of Service Quality, Prices and Perceptions Taste Towards Customer Satisfaction and Loyalty at The Store “Mie Liho Mie Kiro” Gresik - Maimunah, Siti; Sardjono, Sigit (Universitas Kristen Petra dan Ikatan Sarjana Ekonomi Indonesia Cabang Surabaya, 2024)
Marketing is a business activity that consists of a process in planning consumer needs, creating a product that is suitable for marketing, promoting, and distributing products or services. One the efforts made the company in marketing is by being able to meet the desires and needs of consumers, to provide satisfaction and loyalty to consumers who are the main factors in the success of business. Therefore, consumers expect a quality of performance that can provide satisfaction and customer loyalty by providing quality service, price perceptions and tastes that can make consumers interested. In this study the population is all consumers of